2013
DOI: 10.2500/ajra.2013.27.3967
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maxillary Sinus Irrigation on Early Prognostic Factors after Endoscopic Sinus Surgery: A Preliminary Study

Abstract: Maxillary sinus saline irrigation may be effective in the prevention of poor prognostic factors, such as persistent purulent discharge, at the early stages after ESS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Kim et al . found that maxillary sinus saline irrigation may be effective in the prevention of poor prognostic factors, such as persistent purulent discharge, at the early stages after FESS 15 . A number of authority system reviews have already been published 16 …”
Section: Discussionmentioning
confidence: 99%
“…Kim et al . found that maxillary sinus saline irrigation may be effective in the prevention of poor prognostic factors, such as persistent purulent discharge, at the early stages after FESS 15 . A number of authority system reviews have already been published 16 …”
Section: Discussionmentioning
confidence: 99%
“…At present, nasal irrigation using a saline solution is considered to be effective for preventing purulent rhinorrhea, granulation, and polyp recurrence after ESS. 360 Nasal irrigation with budesonide is also an effective postoperative therapy for patients with NP and asthma as evidenced by decreased DSQOL and Lund-Kennedy scores and reduced intake of oral steroids. 361 Furthermore, 83% of the difficult-to-treat CRS patients exhibited satisfactory alleviation of their subjective symptoms, and 75% of the patients showed improvement in DSQOL and endoscopic scores after 500-mL irrigation with 1 mg budesonide in a saline solution, twice daily for 3 months.…”
Section: Nasal Irrigationmentioning
confidence: 99%
“…7 However, the sample size was relatively small (n = 15), and the symptom score was slightly worse after irrigation, which conflicts with the findings of other reports. 1,2,[8][9][10][11] In this study, we used a larger sample size and examined the effect of xylitol nasal irrigation on patients who had undergone ESS or septoplasty (or both). We also compared the extent of nasal symptom relief between the saline and xylitol irrigation groups.…”
mentioning
confidence: 99%